Potential application of kaolin without calcine as greener concrete: A review - Cheng, Yong Heah; Hazlinda, Kamarudin; Mohd Mustafa Al-Bakri, Abdullah; Luqman, Musa, Dr.; Khairul Nizar, Ismail, Assoc. Prof. Dr; Liew, Y. M. (INSInet Publications, 2012)
Link to publisher's homepage at http://www.insipub.com/